TATA KELOLA PAMERAN BERBASIS PROJECT LEARNING PROGRAM STUDI DESAIN KOMUNIKASI VISUAL UNIVERSITAS DIAN NUSWANTORO - Khamadi Khamadi; Agus Setiawan (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2020)
Cultivating exhibitions for visual communication design students is to increase the drive to create and enhance the spirit of student appreciation for the work of students to achieve quality and character in the work. The research objective is to know and understand the governance of project learning-based exhibits to improve the quality of learning and build a climate of appreciation for artwork among Udinus visual communication design students. The research method uses qualitative methods which are more emphasized on observation, interviews, documentation. Through the implementation of project learning-based exhibition governance, learning outcomes in improving quality can be achieved.Key Words: Exhibition, Management, Project Learning